2009
DOI: 10.5194/acp-9-9315-2009
|View full text |Cite
|
Sign up to set email alerts
|

Wildfire smoke in the Siberian Arctic in summer: source characterization and plume evolution from airborne measurements

Abstract: Abstract. We present airborne measurements of carbon dioxide (CO 2 ), carbon monoxide (CO), ozone (O 3 ), equivalent black carbon (EBC) and ultra fine particles over NorthEastern Siberia in July 2008 performed during the YAK-AEROSIB/POLARCAT experiment. During a "golden day" (11 July 2008) a number of biomass burning plumes were encountered with CO mixing ratio enhancements of up to 500 ppb relative to a background of 90 ppb. Number concentrations of aerosols in the size range 3.5-200 nm peaked at 4000 cm −3 a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
118
2
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 124 publications
(126 citation statements)
references
References 49 publications
(61 reference statements)
3
118
2
3
Order By: Relevance
“…4) and more persistent, smoldering peat-fueled fires in Borneo than in North America. A study of Siberian smoke events finds ages ranging from 1 to 13 days with mean 5.5 days (Paris et al, 2009), an order of magnitude greater than ages obtained here. However, these smoke events are not associated with a source fire, and in some cases are located thousands of kilometers from the nearest active fires, so we would classify them as smoke clouds, not plumes (Tosca et al, 2011).…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…4) and more persistent, smoldering peat-fueled fires in Borneo than in North America. A study of Siberian smoke events finds ages ranging from 1 to 13 days with mean 5.5 days (Paris et al, 2009), an order of magnitude greater than ages obtained here. However, these smoke events are not associated with a source fire, and in some cases are located thousands of kilometers from the nearest active fires, so we would classify them as smoke clouds, not plumes (Tosca et al, 2011).…”
Section: Discussionmentioning
confidence: 83%
“…Following the convention described in Tosca et al (2011), we would characterize this smoke as arising from "smoke clouds" rather from than "smoke plumes," as it is not associated with a clear fire source. As expected, older smoke clouds are found further from observed fire locations (Paris et al, 2009). Using a procedure similar to ours, Val Martin et al (2010) found that North American smoke plumes (i.e., clearly differentiated and associated with a fire source) have a median age of 2 h. This study estimates, for the first time, the distribution of plume ages from regularly occurring open fire-generated plumes.…”
mentioning
confidence: 70%
See 3 more Smart Citations